PENGARUH PENGGUNAAN BRAND AMBASSADOR IDOL K-POP (EXO) TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING - Wicaksana, Julio; Asmalidar (Politeknik Negeri Medan, 2024)
This research aims to determine the influence of using the K-Pop Idol (EXO) brand ambassador on purchasing decisions for Scarlett Whitening products. The type of data in this research is quantitative data using a Likert scale. The data collection technique used a questionnaire distributed to 86 finance and banking students majoring in accounting at Medan State Polytechnic who had used Scarlett products. The data analysis technique uses hypothesis testing, correlation coefficient, coefficient of determination, and simple linear regression analysis, which was processed with the help of SPSS 27. This research found that using EXO as a brand ambassador positively impacted purchasing decisions for Scarlett Whitening products, with an influence of 15.5%. The remaining 84.5% is explained by other variables not studied. The results of the simple linear regression analysis show that every time a brand ambassador experiences an increase of 1%, purchasing decisions will also increase by 0.254.